Kaji Eksperimental Solar Chimney Power Plant (SCPP) Dengan Concentrating lens Disusun Dengan Pola Aligned - Fransiskus Asisi Benny Sitinjak; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Solar chimney power plant (SCPP) is an efficient and environmentally friendly renewable energy by utilizing solar energy as its main source. Based on the obtained hypothesis, the use of concentrating lenses can increase the temperature inside the solar collector. With increasing temperature, the speed of air to rotate the turbine blades will increase, so that the power obtained will increase maximally. This tool consists of 4 parts, namely: a buffer made of circular steel reinforcement, a heat sink made of concrete and painted black to absorb more heat and formed in a circle, a transparent cover or collector of clear plastic material, and a concentrating lens with variations of 36 and 21 concentrating lenses. This study aims to determine the temperature increase that occurs in the solar collector using a concentrating lens, to determine the wind power potential and efficiency of the solar collector using 36 concentrating lenses, 21 concentrating lenses and without using concentrating lenses. The results of this research are, by the using of concentrating lens that totalling of 36 and 21, it produces maximum wind power of 3.006 W and 2.478 W with an average of 0.929 W and 0.761 W per day, while without the using of concentrating lens, it produces 1.483 W with an average of 0.486 W per day, and it obtained the collector efficiency by the using of 36 and 21 concentrating lens of 1.122% and 1.016%, and without using a concentrating lens the collector efficiency is obtained 0.775%. Keywords Solar Chimney Power Plant, Concentrating Lens, Solar Radiation